Impact of Chronic Obstructive Pulmonary Disease in surgical outcomes of lung cancer patients undergoing curative intent surgery - Marta Dias Pereira da Costa (2021)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) and lung cancer are prevalent diseases worldwide that coexist in a significant number of patients, largely due to their common risk factors. The best treatment for lung cancer remains curative intent surgery, however concomitant COPD holds an additional challenge. The aim of this paper is to review the available literature on the outcomes that a COPD patient faces after surgery in terms of complications and survival, as well as the impact on their pulmonary function. Methods: With the following query: COPD AND ("Lung Cancer" OR "Lung Neoplasm") AND ("Postoperative Complications" OR "Surgical Outcomes") we identified 282 articles on Pubmed and Scopus. After screening, 39 articles were included in the review. Results/Discussion: The most common complications that a COPD patient faces after surgery are pneumonia, air leak, atrial fibrillation and atelectasis. Furthermore, survival rates of these patients may be diminished. Nevertheless, certain patients with emphysematous changes may experience an improvement of their pulmonary function after surgery, due to the volume reduction effect. Conclusion: COPD carries worse outcomes to patients requiring lung cancer resection surgery. A careful selection of the eligible patients helps to achieve good results both in terms of complications and survival.